Literasi Keuangan Dan Perilaku Keuangan Berpengaruh Terhadap Perilaku Konsumtif Pada Player Call Of Duty: Mobile - Intan Syafira Nur Fauzi; Ari Sulistyowati (Jurnal Kajian Ilmiah, 2022)
This study aims to determine and measure the influence of financial literacy and behavior on consumptive behavior in Call of Duty: Mobile players. The rapid development of the virtual world has become a scourge for its users in seeking entertainment through online games, this has become an opium effect for users of all ages and occupations, making them consumptive actors. This research is a quantitative research, where the object is used as a Call of Duty: Mobile player. The data processing method is carried out using PLS (Partial Least Square). The sampling method used in this study is a non-probability sampling method with the technique used is purposive sampling. The number of samples used in this study amounted to 120 respondents. The design hypothesis was tested through the structural equation model (SEM) in the SmartPLS 3.0 application. The results of the study indicate that financial literacy affects the consumptive behavior of Call of Duty: Mobile players positively and significantly, financial behavior also affects the consumptive behavior of Call of Duty: Mobile players positively and significantly. The results of this study contradict the theory as well as several previous studies where financial literacy and financial behavior should have an influence on consumptive behavior. The results of this study can be a suggestion for further researchers in developing related research to find several other factors that influence consumptive behavior for gamers.